KETERAMPILAN PUKULAN FOREHAND DAN BACKHAND TENIS MEJA MELALUI MODIFIKASI ALAT - Fawzan Anggara (Jurnal Muara Olahraga, 2020)
Abstract The Objective of this research is the skills ability of forehand and backhand blows through modification tools. The method used in this research is Action Research. Techniques of collecting data using quantitative and qualitative data retrieval. The Implementation of this action research involves experts in the areas of physical education, especially the sports table tennis as a collaborator. This research was conducted in two cycles, namely cycle I and cycle II and beginning with observation and preliminary test. The activity in cycle II realized in the form of action II gives the following results: 1) Students have understood the concept of the right forehand and backhand blows. 2) Students are able to perform the stages of the forehand and backhand punches correctly. 3) Students have motivation and passion in implementing learning and showing positive attitudes. The result of this research is the improvement of skill ability forehand and backhand blows through the modification tool. The increase is seen from the average score of the student’s test. For the initial test forehand = 72.11, the cycle I = 74.44 and cycle II = 77.56 & for the initial test backhand = 69.61, cycle I = 72.11 and cycle II = 77. For student learning graduation based on the result of the initial test forehand students who passed are 3 students (10%), cycles I students graduated are 8 students (26.67%) and cycle II students who passed are 27 students (90%). For the initial test result of backhand of the students who passed are 5 students (16.67%), in cycle I the students who passed are 16 students (46.67%) and cycle II students who passed are 27 students (90%). Keywords: Skill Abilities, Table Tennis, Forehand, Backhand, Modification